A reference architecture for real-time performance measurement : an approach to monitor and control manufacturing processes - Karadgi, Sachin (Progress in IS, 2014)
This book describes how manufacturing enterprises, by reinforcing their existing monitoring and control of manufacturing processes, can successfully face the ever-increasing pressure from internal and external environments to maintain their competitive advantage. Numerous performance measurement systems have been elaborated to satisfy these requirements, stressing the importance of financial and operational metrics. It also highlights the fact that research on generating and linking financial and operational metrics, especially in real-time, has not garnered sufficient attention to date. The book follows an approach that integrates enterprises across different levels and departments. By computing and linking the financial and operational metrics in real-time, the book demonstrates how to provide a comprehensive view of an entire enterprise.